2020
DOI: 10.1155/2020/3741019
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of the Antitumor and Immunogenic Properties of Silver and Sodium Dichloroacetate Combination against Melanoma

Abstract: Our main focus was to evaluate the efficacy of silver and sodium dichloroacetate as dual-function agents to be used in melanoma treatment. This strategy is designed to increase the activity of these two compounds that affect DNA integrity and the mitochondria at different levels. Furthermore, we evaluated if the cell death mechanism induced by our treatments was immunogenic cell death. To evaluate antitumor efficacy, we assessed tumor volume and production of tumor necrosis factor-α, nuclear factor κ B (both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These findings reinforce the premise that the antioxidant properties of DCA are implicated in the alleviation of oxazolone-induced colitis. In accordance, previous reports have described the considerable antioxidant activity DCA in several experimental models (Torres-Cavazos et al 2020 ; Zhao et al 2021 ; Li et al 2020 ). The observed reduction in NO levels after treatment with DCA may be attributed to its suppressive impact on NF-κB, which is responsible for enhancing the transcription of iNOS; the primary contributor to NO production during inflammatory processes (Saed et al 2011 ; Mercken et al 2009 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings reinforce the premise that the antioxidant properties of DCA are implicated in the alleviation of oxazolone-induced colitis. In accordance, previous reports have described the considerable antioxidant activity DCA in several experimental models (Torres-Cavazos et al 2020 ; Zhao et al 2021 ; Li et al 2020 ). The observed reduction in NO levels after treatment with DCA may be attributed to its suppressive impact on NF-κB, which is responsible for enhancing the transcription of iNOS; the primary contributor to NO production during inflammatory processes (Saed et al 2011 ; Mercken et al 2009 ).…”
Section: Discussionsupporting
confidence: 92%
“…ELISA and biochemical analysis were performed as previously reported and results showed that DCA significantly reduced IL-1β by 36% (Forteza et al 2023 ), IL-13 by 40% (Ostroukhova et al 2012 ) (Fig. 4 A), and NO levels by 30%, as well as MPO activity by 30% (Saed et al 2011 ; Torres-Cavazos et al 2020 ) (Fig. 4 B).…”
Section: Resultsmentioning
confidence: 67%
“…On another side, there are reports of AgNPs reduced with glucose and their capacity to induce alarmins related to ICD, however, when the gold standard is performed, the ICD is not generated [14]. This possible mechanism of action could appear if the quantity or quality of alarmins or tumor neoantigens is affected by treatment, as in B16F10 cells treated with colloidal silver / AgNPs as a prophylactic vaccine in vivo by Torres et al, 2020 and García et al, 2023, respectively [14,30], not preventing tumor implantation in mice of the C57BL/6 strain, despite alarmins presence. However, in our study, a certain grade of immunity is developed as it delays tumor growth, indicating that some mechanisms, such as mentioned ahead, can be implicated and should be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Moises Armides Franco-Molina and others (2020) conducted an in vivo assessment of the silver and sodium dichloroacetate combination antitumor and immunogenic properties against melanoma, the use of which in a complex is aimed at achieving synergism and increasing both compounds' activity, the action mechanism of which is to affect the DNA and mitochondria integrity at various levels [63,64]. During the antitumor efficacy determination, the tumour volume, the tumour necrosis factor-α, nuclear factor κB production (both factors were determined by the enzyme immunoassay method), and the nitric oxide level (by the nitrate/nitrite colourimetric analysis method) were evaluated; for immunogenic cell death, the danger-associated molecular structures release was assessed using immunohistochemistry and flow cytometry.…”
Section: Biological Activity Of Dichloroacetic Acid Derivativesmentioning
confidence: 99%